Reconnaître une déesse ailée au caducée - Annaïg Caillaud (Cahiers Mondes Anciens, 2016)
A small corpus of images of vases created in the Fifth Century BC raises the question of how to identify or confuse winged goddesses holding a caduceus, since these are often difficult to differentiate. The survey focuses on three divine figures: Iris the messenger, Nike the Victory and Eos the Dawn. However in Greek polytheism, especially on the level of understanding of Greek religion that represents the images of Gods, these three goddesses cannot be reduced to such simple roles. Whether by associating a representation and an inscription, or by adding an attribute to a known iconographic scene, the authors wanted to identify one or another goddess. This is why the images could sometimes lead to confusion. It must therefore take various works to try to understand what the ancient painters wanted to show through what the modern researchers wanted to demonstrate.